2022
DOI: 10.3390/plants11010141
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Metabolism of Wine Grape Trincadeira: Impact of Infection with Botrytis cinerea

Abstract: The aroma of grapes is cultivar dependent and is influenced by terroir, vineyard practices, and abiotic and biotic stresses. Trincadeira is a non-aromatic variety associated with low phenolic content and high sugar and organic acid levels. This cultivar, widely used in Portuguese wines, presents high susceptibility to Botrytis cinerea. This work aimed to characterise the volatile profile of Trincadeira grapes and how it changes under infection with B. cinerea. Thirty-six volatile organic compounds were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…Shiojiri et al (2006) showed that overexpression of hydroperoxide lyase (HPL) in Arabidopsis led to higher resistance of transgenic plants to Botrytis cinerea, which may be due to the increasing contents of C6 VOCs emitted by plants after infection, reflecting the assumed role of VOCs metabolism in grape defense mechanism. However, our results are in agreement with those reported by Santos et al (2022), who found that hexanal and (E)-2-hexenal decreased greatly both in free or glycosylated after infection with Botrytis cinerea, suggesting that C6-VOCs can be used as a stress signal for plant biological stress. Schueuermann et al (2018) also confirmed the concentration of (E)-2-hexenal in V. vinifera cv.…”
Section: The Changes In C6-volatile Organic Compoundssupporting
confidence: 93%
See 4 more Smart Citations
“…Shiojiri et al (2006) showed that overexpression of hydroperoxide lyase (HPL) in Arabidopsis led to higher resistance of transgenic plants to Botrytis cinerea, which may be due to the increasing contents of C6 VOCs emitted by plants after infection, reflecting the assumed role of VOCs metabolism in grape defense mechanism. However, our results are in agreement with those reported by Santos et al (2022), who found that hexanal and (E)-2-hexenal decreased greatly both in free or glycosylated after infection with Botrytis cinerea, suggesting that C6-VOCs can be used as a stress signal for plant biological stress. Schueuermann et al (2018) also confirmed the concentration of (E)-2-hexenal in V. vinifera cv.…”
Section: The Changes In C6-volatile Organic Compoundssupporting
confidence: 93%
“…Chardonnay grapes decreased after infection with Botrytis cinerea in two out of three vintages. We speculated that pathogenic fungal infestation could manipulate the level of C6-VOCs to reduce the defense effect of fruit, because low concentrations of (E)-2-hexenal may promote mycelium growth (Santos et al, 2022). Moreover, previous studies also showed that green aroma gradually decreased with fruit maturation, which was also a possibility for the decrease of hexanal and (E)-2-hexenal (Agudelo-Romero et al, 2013).…”
Section: The Changes In C6-volatile Organic Compoundsmentioning
confidence: 99%
See 3 more Smart Citations